Bleeding complications related to external ventricular drainage placement in patients with ruptured intracranial aneurysms: a single-center study - Tang, Yue; Zhong, Xiangping; Lin, Tingting; Zuo, Fujun; Fu, Min; Wang, Li; Yu, Xiaodu; Liu, Dong; Zhang, Jincan (Frontiers in Surgery, 2024)
ObjectiveAcute aneurysmal rupture can be treated with endovascular therapy or surgical clipping. For patients with concurrent acute hydrocephalus, the placement of an external ventricular drainage (EVD) is required. This study aims to investigate the impact of pre-treatment EVD placement on rebleeding in ruptured aneurysms and to examine the influence of dual antiplatelet therapy and the sequencing of dual antiplatelet therapy with EVD placement on EVD-related hematomas.MethodsWe reviewed the clinical data of 83 patients with ruptured aneurysms who underwent EVD placement from a total of 606 aneurysm patients consecutively admitted between January 2018 and January 2023. The analysis focused on the impact of pre-treatment EVD placement on aneurysmal rebleeding and the effect of dual antiplatelet therapy and its sequencing with EVD placement on EVD-related hematomas.ResultsAmong the 503 patients with ruptured aneurysms, 83 required EVD placement. EVD was placed before aneurysm treatment in 63 patients and after treatment in 20 patients. The number of aneurysmal rebleeding cases in the pre-treatment EVD group and non-EVD group was 1 (1.6%) and 20 (4.8%), respectively (p = 0.406). 31 patients (37.3%) underwent stent-assisted embolization or flow diversion requiring dual antiplatelet therapy, while 52 patients (62.7%) underwent simple embolization or surgical clipping without antiplatelet therapy. EVD-related hematomas occurred in 14 patients (16.9%), with 10 cases (32.3%) in those receiving dual antiplatelet therapy and 4 cases (7.7%) in those not receiving antiplatelet therapy (p = 0.01). Among 16 patients who had EVD placed before dual antiplatelet therapy, 4 (25%) developed EVD-related hematomas. Of the 15 patients who had EVD placed after dual antiplatelet therapy, 6 (40%) developed EVD-related hematomas (p = 0.458).ConclusionIn patients with aneurysmal subarachnoid hemorrhage (aSAH) and acute hydrocephalus, the placement of EVD before aneurysm treatment does not increase the risk of rebleeding. However, dual antiplatelet therapy increases the risk of EVD-related hematoma, and the sequence of EVD placement relative to dual antiplatelet therapy does not appear to significantly affect the outcome of EVD-related hematoma.